2017
DOI: 10.1186/s12941-016-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of ESBL-producing Escherichia coli carrying aminoglycoside resistance genes in urinary tract infections in Saudi Arabia

Abstract: BackgroundThe infection and prevalence of extended-spectrum β-lactamases (ESBLs) is a worldwide problem, and the presence of ESBLs varies between countries. In this study, we investigated the occurrence of plasmid-mediated ESBL/AmpC/carbapenemase/aminoglycoside resistance gene expression in Escherichia coli using phenotypic and genotypic techniques.MethodsA total of 58 E. coli isolates were collected from hospitals in the city of Makkah and screened for the production of ESBL/AmpC/carbapenemase/aminoglycoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
86
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 42 publications
23
86
4
Order By: Relevance
“…The association of ESBL and AmpC phenotypes with increased prevalence of 276 aminoglycoside resistance has been reported [52]. In our study we identified a significant isolates were significantly more resistant to ceftazidime than ESBL isolates.…”
supporting
confidence: 66%
“…The association of ESBL and AmpC phenotypes with increased prevalence of 276 aminoglycoside resistance has been reported [52]. In our study we identified a significant isolates were significantly more resistant to ceftazidime than ESBL isolates.…”
supporting
confidence: 66%
“…Extended spectrum beta-lactamase Enterobacteriaceae are also common among hospitalized pilgrims. During the 2014-2015 Hajj, 47% of pilgrims attending hospitals for urinary tract infections showed blaCTX-M genes in E. coli isolates [59].…”
Section: Hajj and Antimicrobial-resistant Bacteriamentioning
confidence: 99%
“…However, a discrepancy between phenotypic and genotypic methods was noted, which emphasizes the imperative need of molecular methods to obtain reliable interpretation of antimicrobial resistance profile. The difference observed in detection of resistance may be justified by the lower sensitivity of phenotypic method and the influence of environmental factors on the incidence of resistance (Alyamani et al, 2017). The lack of constant sensitivity of different phenotypic methods has been emphasized by some studies (Ravi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%